2010
DOI: 10.1177/0009922809360926
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Pediatric Lead Screening: Implications From a Web-Based Survey of Vermont Pediatricians

Abstract: The pernicious effects of lead on child health are well documented. The Vermont Department of Health (VDH) recommends screening all 12-and 24-month-old children for elevated blood lead levels (BLL). In 2006, only 41.4% of 24-month-old Vermont children were screened. To identify barriers preventing pediatricians from performing blood lead screening, a survey was distributed to Vermont primary care pediatricians-divided in higher and lower screening groups. Vermont pediatricians were more likely to be lower scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…19 Another study found that pediatricians were less likely to test if they believed that adverse health effects did not occur at BLLs of less than 10 μg/dL, disagreed with the state's testing recommendations, and served a low percentage of Medicaid-enrolled patients. 20 These studies further demonstrate the need for determining the most successful policies to inform providers' testing decisions.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…19 Another study found that pediatricians were less likely to test if they believed that adverse health effects did not occur at BLLs of less than 10 μg/dL, disagreed with the state's testing recommendations, and served a low percentage of Medicaid-enrolled patients. 20 These studies further demonstrate the need for determining the most successful policies to inform providers' testing decisions.…”
mentioning
confidence: 95%
“…One study found that although most providers were aware of testing requirements for Medicaid-enrolled children, one-third erroneously believed their practice was in a low-risk area and did not test 19. Another study found that pediatricians were less likely to test if they believed that adverse health effects did not occur at BLLs of less than 10 μg/dL, disagreed with the state's testing recommendations, and served a low percentage of Medicaid-enrolled patients 20. These studies further demonstrate the need for determining the most successful policies to inform providers' testing decisions.…”
mentioning
confidence: 99%
“…11 – 13 Some clinicians use screening questionnaires to identify children at risk of lead exposure who should receive blood lead testing, but these are of limited predictive utility. 14 A few studies 15 17 have found substantial variation in whether clinicians choose to test children’s blood for lead and have shown that this decision is a function of physicians’ knowledge, practice setting, patient demographics, and financial incentives. Second, investigations to identify possible sources of lead exposure are only triggered if a child’s BLL is above an “action level,” usually the U.S. Centers for Disease Control and Prevention (CDC) reference value.…”
Section: Introductionmentioning
confidence: 99%
“…The burden for prevention lies primarily on public health departments, implementation of policies by local organizations, and health care providers responsible for screening [9]. However, adherence to screening requirements remains surprisingly low [10,11]: roughly 40% of Medicaid-enrolled children do not receive screening, despite being mandated to do so through the Early Periodic Screening Diagnostic and Testing (EPSDT) program [6]. Overall, low income and minority children remain at higher risk of lead exposure [6].…”
Section: Introductionmentioning
confidence: 99%